Fatores ambientais e individuais associados à vacinação contra a Hepatite B em gestantes - Thales Philipe Rodrigues da Silva (2018)
Introduction: Hepatitis B vaccine (recombinant) (HBV) is the most effective way to prevent hepatitis B virus infection. Vaccination status is influenced by intrinsic individual factors and contextual factors. Objective: To analyze the environmental and individual factors associated with hepatitis B vaccination in pregnant women. Methods: This is a systematic review and meta-analysis of the literature, and epidemiologicalstudy with a cross-sectional design. Regarding the systematic review, the search strategy was performed in EMBASE and MEDLINE. The selection included: pregnant women; cohort or cross-sectional studies; studies with data on the vaccination rate against hepatitis B and related risk factors. Fixed and random effects models were applied, according to the methodological heterogeneity between the studies. Heterogeneity between the studies was evaluated using the Q statistic and I-square tests. For the epidemiological study, we used the data of 266 postpartum women who participated in the study: "Birth in Belo Horizonte: Birth and Birth Survey". Data were collected in 11 maternity hospitals in Belo Horizonte, Minas Gerais. The presence of HBV registry in the prenatal care booklet was used as an indirect measure of a pregnantwoman´s immunization and was considered as an outcome. For the detection of risk cluster for the presence or absence of HBV registry , spatial scanning technique was used. Subsequently, individual and environmental variables were compared between thecoverage areas of the Basic Health Units (CAs - BHUs). In order to evaluate the association between the factors influencing HBV vaccination of pregnant women, multilevel logistic regression was performed. Results: The systematic review evidenced 7 studies that met all the inclusion criteria and 4 were included in the meta-analysis.Pooled analysis showed a positive association between higher education level and hepatitis B vaccination rate (OR: 1.46, 95% CI 1.121.92). There was no significant heterogeneity between the studies (I2 = 18%). In the epidemiological study, the prevalence of non- HBV was 88.34%. In the spatial scan analysis, a cluster of high prevalence of HBV was observed, and the probability of finding a puerperium withHBV registration in the cluster was 8.33 times compared to other CAs - BHUs. Comparative analysis showed that the paid work and the number of consultations during prenatal care were positively associated with HBV. In the final multilevel logistic model, pregnant women residing in CAs - BHUs with higher crime rate presented a greater chance of non- HBV. Conclusion: Environmental factors, such as residing in anarea of high crime rates, and individual factors, such as higher education level, paid work and greater number of prenatal consultations, were determinant for HBV rates in pregnant women.